Quality evaluation of Cistanche deserticola and rice wine-steamed products: drying kinetics, intelligent sensory, and chemometrics analysis - Jiang, Zhangli; Tang, Shiyuan; Wu, Xu; Zhang, Hui; Zhang, Xinyi; Ma, Zihan; Bian, Xiaohui; Wang, Hui; Chai, Xin; Wang, Yuefei; Dou, Zhiying (Frontiers in Nutrition, 2026)
BackgroundCistanche deserticola (CD), a functional plant with homology of medicine and food, is used for reinforcing kidney to strengthen yang and loosening bowel to relieve constipation. It is ordinarily processed with rice wine-steamed, which is known as wine-steamed CD (W-CD) to enhance effects in clinical practice. Nevertheless, timely processing of CD is an effective means to ensure quality; the processing techniques also played a crucial role in influencing the quality of CD and its products, which require further investigation. This study aimed to explore suitable drying methods for the efficient production of CDs and W-CDs.MethodsHerein, the fresh CD is collected and both CD and W-CD are prepared, which all drying mainly included forced-air drying (FAD, at 40, 60, and 80 °C), far-infrared air drying (FID, at 40, 60, and 80 °C), vacuum microwave drying (VMD, at 50, 55, and 60 °C), vacuum freeze drying (VDF), sun-drying (SD) respectively. Furthermore, drying kinetics were employed to analyze drying characteristics, establishing Weibull function models for different processing methods of CD and W-CD. Combining intelligent sensory technologies (E-nose, E-tongue, color difference meter) with texture analyzers, and employing scanning electron microscopy, the trait characteristics and microstructural features were investigated to examine the effects of different drying methods on CD and W-CD. The components content of Echinacoside, Cistanoside A, Tubuloside A, Verbascoside, Isoverbascoside, 2’-Acetylverbascoside, and total polysaccharides are analyzed by high-performance liquid chromatography (HPLC) and ultraviolet–visible spectrophotometry (UV), and the total extracts are also measured. Above those are combined with chemometrics to obtain important factors analysis to differentiate samples of quality.ResultsThe Weibull model of drying dynamics is established successfully for CD and W-CD drying processing. The microstructure, rehydration rate (RR, %), and porosity (%) of CD are significantly influenced by rice wine-steamed processing, as are the sweetness (ANS) and content of phenylethyl glycoside, which are also increased. The best drying condition for CD is FAD60-80 °C, and W-CD is FID 40 °CConclusionOur study, which is comprehensive in comparing the quality of CD and W-CD across different drying processes based on “color—odor—taste—component content,” revealed that improving quality can enhance the production of fresh CD. Besides, intelligent sensory technology can provide a foundation for future quality control of CD and W-CD.